Hubungan Kompensasi Tunjangan Profesi Dan Disiplin Kerja Terhadap Kinerja Guru: Survei Di Madrasah Tsanawiyah/MTs Di Kota Bekasi - Farida Hanun (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This study aims to know the relationship of the compensation of profession allowance, working diciplines, toward the performance of the Madrasah Tsanawiyah (Islamic Junior High School/MTs) teachers. This study is done at MTs Negeri (State Islamic Junior High School) in Bekasi City with the respondent of 20 madrasah teachers (which in the status of Pegawai Negeri Sipil (Civil State Officer/PNS)). This research uses random sampling technique. The result of this research shows: 1) the existence of positive relationship between the compensation of profession allowance and the teacher performance, 2) the existence of positive relationship between the working dicipline and the madrasah teacher performance, 3) the existence of positive relationship between the compensation of profession allowance and the working diciplines together with the performance of madrasah teachers. Penelitian ini bertujuan untuk mengetahui hubungan kompensasi tunjangan profesi, disiplin kerja, terhadap kinerja guru Madrasah Tsanawiyah (MTs). Penelitian ini dilakukan pada MTs Negeri di Kota Bekasi dengan responden 20 guru madrasah (status pegawai negeri sipil atau PNS). Sampel menggunakan teknik random sampling. Hasil penelitian menunjukkan: 1) terdapat hubungan positip antara kompensasi tunjangan profesi dengan kinerja guru, 2) terdapat hubungan positip antara disiplin kerja dengan kinerja guru madrasah, 3) terdapat hubungan positip antara kompensasi tunjangan profesi dan disiplin kerja secara bersama-sama dengan kinerja guru madrasah.